Modeling and Behavior Analysis of a Membraneless Fuel Cell. (9th February 2012) - Flores-Rivera, Ciro-Filemon
Abstract : Membraneless fuel cells are examples of microelectromechanical systems (MEMSs) that can be considered as alternate energy sources. Applications include microfluidic-based devices like miniaturized laboratories, sensors, or actuators to be used in medicine or agronomy. This paper presents a mathematical model for this type of cells based on the governing physical laws. It includes fluid dynamics, electric charge distribution and electrostatics modeled by the Navier-Stokes, Nernst-Planck, and Poisson equations, respectively. A robust numerical algorithm is proposed to solve the model. Two cases are discussed: allowing electrochemical reactions on one of the electrodes and the simpler situation of null exchange current density. An initial characterization for the behavior of membraneless fuel cells is achieved concerning to prevalence of velocity and electric field, use of non-Newtonian fluids, relationship to initial conditions for some variables, general profile for conductivity and electric density, and linear dependence on current density under specific conditions.